Nicorandil Inhibits Osteoclast Formation Base on NF-κB and p-38 MAPK Signaling Pathways and Relieves Ovariectomy-Induced Bone Loss - Xu, Shenggui; Cao, Xiankun; Yu, Zhenxing; He, Wenxin; Pang, Yichuan; Lin, Wang; Chen, Zhiqian; Guo, Weizhong; Lu, Xiongwei; Lin, Chengshou (Frontiers in Pharmacology, 2021)
Osteolytic bone disorders are characterized by an overall reduction in bone mineral density which enhances bone ductility and vulnerability to fractures. This disorder is primarily associated with superabundant osteoclast formation and bone resorption activity. Nicorandil (NIC) is a vasodilatory anti-anginal drug with ATP-dependent potassium (KATP) channel openings. However, NIC is adopted to manage adverse cardiovascular and coronary events. Recent research has demonstrated that NIC also possesses anti-inflammatory peculiarity through the regulation of p38 MAPK and NF-κB signaling pathways. Both MAPK and NF-κB signaling pathways play pivotal roles in RANKL-induced osteoclast formation and bone resorption function. Herein, we hypothesized that NIC may exert potential biological effects against osteoclasts, and revealed that NIC dose-dependently suppressed bone marrow macrophage (BMM) precursors to differentiate into TRAP+ multinucleated osteoclasts in vitro. Furthermore, osteoclast resorption assays demonstrated anti-resorptive effects exhibited by NIC. NIC had no impact on osteoblast differentiation or mineralization function. Based on Biochemical analyses, NIC relieved RANKL-induced ERK, NF-κB and p38 MAPK signaling without noticeable effects on JNK MAPK activation. However, the attenuation of NF-κB and p38 MAPK activation was sufficient to hamper the downstream induction of c-Fos and NFATc1 expression. Meanwhile, NIC administration markedly protected mice from ovariectomy (OVX)-induced bone loss through in vivo inhibition of osteoclast formation and bone resorption activity. Collectively, this work demonstrated the potential of NIC in the management of osteolytic bone disorders mediated by osteoclasts.